Microbiota Influences Morphology and Reproduction of the Brown Alga Ectocarpus sp. - Tapia, Javier E.; González, Bernardo; Goulitquer, Sophie; Potin, Philippe; Correa, Juan A. (Frontiers in Microbiology, 2016)
Associated microbiota play crucial roles in health and disease of higher organisms. For macroalgae, some associated bacteria exert beneficial effects on nutrition, morphogenesis and growth. However, current knowledge on macroalgae-microbiota interactions is mostly based on studies on green and red seaweeds. In this study, we report that when cultured under axenic conditions, the filamentous brown algal model Ectocarpus sp. loses its branched morphology and grows with a small ball-like appearance. Nine strains of periphytic bacteria isolated from Ectocarpus sp. unialgal cultures were identified by 16S rRNA sequencing, and assessed for their effect on morphology, reproduction and the metabolites secreted by axenic Ectocarpus sp. Six of these isolates restored morphology and reproduction features of axenic Ectocarpus sp. Bacteria-algae co-culture supernatants, but not the supernatant of the corresponding bacterium growing alone, also recovered morphology and reproduction of the alga. Furthermore, colonization of axenic Ectocarpus sp. with a single bacterial isolate impacted significantly the metabolites released by the alga. These results show that the branched typical morphology and the individuals produced by Ectocarpus sp. are strongly dependent on the presence of bacteria, while the bacterial effect on the algal exometabolome profile reflects the impact of bacteria on the whole physiology of this alga.